Prevalence of Foreign Bodies in the Ear, Nose and Throat in Alramadi City (Medico Legal Update, 2020)
Background: Foreign body in ENT refers to an object which settles within head orifices which includes theear, nose, or throat.Aim: Compare the incidence of various Foreign Bodies in the Ear, Nose and Throat and the type of anesthesiarequired for removal in alramadi teaching hospital.Method: This cross-sectional study was conducted on 100 patients who presented with complaints of foreignbody insertion/impactionor ingestion in ear or nose or throat in alramadi teaching hospital.Results: These cases comprised of 64 (64%) males & 36 (36%) females having male: female ratio= 1.77:1. Out of all patients 56 (56%) presented with ear foreign bodies, 33 patients (33%) presented with nasalcavity foreign bodies, 11 patients (11%) presented with the throat (oropharyngeal/hypopharyngeal) foreignbodies. General anesthesia was required in 8 cases (8%) while the rest removed by senior house officersunder supervision by ENT specialists or Consultants without GA.Conclusion: Foreign bodies considered an important challenge to otolaryngologist especially in childrenwho represented the most commonly affected age.